HUBUNGAN ANTARA TINGKAT STRES DAN INDEKS MASSA TUBUH PADA PERAWAT - Ika Nopa; Yulia Afrina Nasution; Nanda Sari Nuralita; Mila Trisna Sari; Pinta Pudiyanti Siregar (Jurnal Ilmu Keperawatan Komunitas, 2022)
Abstract One of professions that exposed to high psychosocial stressors in the workplace is nurse. Long-term stress is thought to be a risk factor for obesity through activation of the HPA axis and cortisol secretion. Stress is a public health problem that can be considered in preventing obesity. The purpose of this study was to determine the effect of stress on body mass index in nurses. This study uses a quantitative method with a cross-sectional study design. The samples were taken using the total sampling method, namely all nurses at the X General Hospital in North Sumatra. The stress variable was measured by the Perceived Stress Scale and the Body Mass Index (BMI)  was determined by the Asia-Pacific classification BMI criteria. The collected data were analyzed by linear regression test. The results showed that there was an effect of stress on nurses' BMI. Work stress management on nurses needs to be done and will have an impact on their mental and physical health.   Keywords: Stress, Nurse, Body Mass Index